"SLEEP UNVEILED: EXPLORING THE VITAL ROLE OF ENVIRONMENTAL CONDITIONS IN SLEEP HEALTH - A COMPREHENSIVE REVIEW" - Anju Sharma; Amandeep Kaur; Jyoti Rana; Akanksha Arya; Dr Jyoti Arora (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Sleep quality and overall well-being are intimately linked, with environmental conditions playing a pivotal role in shaping the restorative nature of sleep. This review article synthesizes current research to explore the multifaceted relationship between environmental factors and sleep health. By analyzing a diverse range of studies, we highlight the significant impact of ambient noise, light exposure, temperature, air quality, and comfort on sleep patterns and sleep-related disorders. Homelessness often exposes individuals to suboptimal sleeping environments, characterized by excessive noise, exposure to harsh weather, and lack of safety. This vulnerable population’s sleep health can be severely compromised, contributing to physical and mental health issues. Addressing the environmental influences on sleep quality within the homeless community is not only a matter of health equity but also underscores the broader significance of creating safe and conducive sleeping spaces for marginalized individuals